Reinventing new order: Turkish revisionist aspirations in the MENA region through a constructivist lens: 2002–2022 - Natalia Sharova; Ronen A. Cohen (Cogent Arts & Humanities)
In recent decades, Turkish foreign policy has pursued a more independent and ambitious foreign policy that can be considered revisionist. This study aims to reveal how Türkiye constructed its revisionist foreign policy toward the MENA region in the last two decades (2002–2022). It also considers the changing Turkish identity in the AKP’s period from pro-Western and Kemalist to neo-Ottoman and Islamic as a key factor in examining Turkish foreign policy in the region. Thematic analysis is used to define the major patterns of Turkish revisionism construction. As a result, three interconnected main themes, the main pillars in Türkiye’s construction of its revisionist aspiration in the MENA, were identified: Turkish historical responsibility, justice, and anti-colonialism. This investigation will contribute to a more detailed understanding of Türkiye’s vision, which has impacted Turkish foreign policy and led to the renovation of the regional balance of power.